Influence of Both Soil Properties and Geometric Parameters on Failure Mechanisms and Stability of Two-Layer Undrained Slopes - Shuangfeng Guo; Ning Li; Wenpeng Liu; Zongyuan Ma; Naifei Liu; Gao Lv (Advances in Materials Science and Engineering)
The stability of the two-layer undrained clay slopes should be given considerable attention since they are commonly observed in nature and in manmade structures, and they traditionally have low stability. Therefore, with the elastoplastic finite element method, this paper thoroughly explores the influence of the soil strength parameter cu, slope angle β, and slope depth ratio DH on the slope stability and failure mechanisms by the wide-ranging parametric changes. The aims of this study are also to find the critical strength ratio (cu2/cu1)crit and the maximum values of the stability number Nc that were observed in the parametric studies. Numerical results are displayed in the form of charts to give Nc and (cu2/cu1)crit as a function of cu, β, and DH. Moreover, influences of DH and β on Nc and failure mechanisms are examined in this study. The results of numerical analysis demonstrate that cu2/cu1 significantly affects both the critical failure mechanism and the stability of the two-layer undrained slope. Improved knowledge of the location of the critical failure mechanism allows for accurately estimating the stability of the two-layer undrained slopes for future strengthening measurements to preserve stability.